Design of efficient metal-free organic dyes having an azacyclazine scaffold as the donor fragment for dye-sensitized solar cells - Biswas, Abul Kalam; Barik, Sunirmal; Sen, Anik; Das, Amitava; Ganguly, Bishwajit (Journal of Physical Chemistry C, 2014)
The energy conversion efficiency of dye-sensitized solar cells derived from organic dye molecules has seen immense interest recently. In this work, we report a series of organic donor molecules with enhanced energy conversion efficiency using ?-spacers and cyanoacrylic acid as an anchoring group (2-6). Density functional theory (DFT) and time-dependent DFT calculations of these molecules have been performed to examine their electronic structures and absorption spectra before and after binding to the semiconductor titanium dioxide surface. The computational results suggest that dyes 4 and 6 have a larger driving force (Delta G(inject) = -1.66 and -1.80 eV, respectively) and light-harvesting efficiency (LHE = 0.99) in the series of donor molecules studied. Thus, these dyes should possess a larger short-circuit photocurrent density (J(sc)) compared to the other examined dyes. The reported Delta G(inject) (-1.62 eV) and LHE (0.98) for compound 1, calculated with the same level of theory, were lower than those of the designed 4 and 6 dyes. Furthermore, the DFT calculations showed that the open-circuit photovoltage (V-oc) is improved with the vertical dipole moment and number of photoinjected electrons for 4 and 6. Dyes 4 and 6 are expected to exhibit high solar-energy-to-electricity conversion.